A study on competitor analysis of Syarikat Perniagaan Perabot Nuri Sdn Bhd Tebobon, Sabah / Suziana Sandhu - Sandhu, Suziana (2008)
This research will be conducted to study on competitor analysis of Syarikat Perniagaan Perabot Nuri Sdn Bhd (SPPN) Tebobon , Sabah. I have chosen this topic due to interest in knowing what customers have to say about the overall services , pricing , marketing strategies and product quality provided by Syarikat Perniagaan Perabot Nuri Sdn Bhd (SPPN). The data will be collected by interviewing the employee using questionnaire. Observation also will be conducted during the study and the problem will be identified immediately. Besides that, the relationships between dependent an independent variables also will be discuss in more detail in this research. Where the dependent variables is differential advantage and independent variables are abilty to produce, ability to manage and ability to market. From the data collection, the company will discover their weaknesses and can improve the marketing strategies while make a right decision. Software called Statistic Package for Social Science (SPSS) will be used to analyze data from the questionnaire. In overall , the research is general in nature which can be quite subjective as it will just cover the surface or basic attributes identified through the theoretical framework. It was through the findings of the research , either directly or from cross-tabulation that, researcher my progress deeper in a specific area if he may wish or allowed to continue researching further.